Eagle syndrome - Mohammad Akheel; Suryapratapsingh Tomar (Wolters Kluwer Medknow Publications, 2013)
Elongation of the styloid process is a very rare clinical phenomenon, affecting 4% of the overall population. The etiopathogenesis of this syndrome is still an enigma although several theories are proposed in the literature. Clinical manifestations of this syndrome occur only in 4-10% of the affected population. If it occurs, an appropriate clinical diagnosis can be made. Most commonly, this syndrome is seen in routine radiographic investigations with elongation of the styloid process, which may be unilateral or bilateral. We report a case of a 45-year old female who had dysphagia with vague cervicofacial pain and was diagnosed with Eagle's syndrome.